Assistance in Making Promotional Media Using Information Technology to Support Competitiveness Digital Marketing for MSMEs: Pendampingan Pembuatan Media Promosi Menggunakan Teknologi Informasi untuk Mendukung Daya Saing Digital Marketing pada UMKM - Dewi, Sofia (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
With the development of the internet, information technology has also undergone a significant transformation in the global marketing paradigm. Before the adoption of this framework, business operators generally used conventional and traditional promotional methods. However, with the emergence of the digital era, traditional approaches have been replaced through digital marketing, involving marketing activities using various social media. The use of social media as a promotional strategy has become an optimal method to expand the market or reach more customers. Micro, Small, and Medium Enterprises (MSMEs) can expand the marketing of their products through digital platforms, especially on various social media channels such as TikTok and Instagram. It is hoped that this can accelerate the transformation of MSMEs in Indonesia towards the digital era. However, not all MSME products can be widely known by the public, and the main cause is the suboptimal utilization of social media as a promotional tool. This research aims to understand the benefits that make social media, especially TikTok and Instagram, effective promotional tools, especially for MSMEs. The method used in this research is a qualitative method. The utilization of social media, especially TikTok and Instagram, for business operators can provide advantages, including serving as a promotional or marketing tool, enabling the establishment of personal relationships with consumers, serving as a means of collecting consumer data, and conveying information or responses to consumers.